Combination of ablative fractional laser and daylight‐mediated photodynamic therapy for actinic keratosis in organ transplant recipients – a randomized controlled trial. (1st February 2015) - Togsverd‐Bo, K.; Lei, U.; Erlendsson, A.M.; Taudorf, E.H.; Philipsen, P.A.; Wulf, H.C.; Skov, L.; Hædersdal, M.
Summary: Background: Topical photodynamic therapy (PDT) for actinic keratoses (AK) is hampered by pain during illumination and inferior efficacy in organ‐transplant recipients (OTR). Objectives: We assessed ablative fractional laser (AFL)‐assisted daylight photodynamic therapy (PDT) (AFL‐dPDT) compared with daylight PDT (dPDT), conventional PDT (cPDT) and AFL alone (AFL) in field treatment of AK in OTR. Methods: In each patient, four areas in the same region were randomized to one treatment with AFL‐dPDT, dPDT, cPDT and AFL. AFL was delivered with a 2940‐nm AFL at 2·3 mJ per pulse, 1·15 W, two stacks, 50‐μs pulse‐duration, 2·4% density. In dPDT and AFL‐dPDT, methyl aminolaevulinate (MAL) was applied for 2·5 h without occlusion during daylight exposure. For cPDT, MAL was occluded for 3 h followed by red‐light (630 nm) irradiation at 37 J cm −2 . The primary end‐point was complete response (CR) 3 months post‐treatment. Results: Sixteen patients with 542 AK (grades I–III) in field‐cancerized skin of the scalp, chest and extremities were treated during August and September 2012. After 3 months, CR (AK I–III) rates were 74% after AFL‐dPDT, 46% after dPDT, 50% after cPDT and 5% after AFL ( P < 0·001). CR rates in AFL‐dPDT, dPDT and cPDT were also significantly different ( P = 0·004). Median maximal pain scores differed significantly during AFL‐dPDT (0), dPDT (0), AFL (0) and cPDT (5) ( P < 0·001). Erythema and crusting were more intense following AFL‐dPDT than dPDT and cPDT, but only transient hypopigmentation was observed. Conclusions: AFL‐dPDT is a novel PDT modality that enhances CR with excellent tolerability compared with dPDT and cPDT in difficult‐to‐treat AK in OTR.